Management of Patients with Chronic Heart Failure and Diabetes Mellitus - E. V. Reznik; T. L. Nguyen; G. N. Golukhov (Столичная издательская компания, 2021)
Chronic heart failure (CHF) occurs in 4.3-28% of patients with diabetes mellitus and is most often associated with the presence of coronary heart disease, arterial hypertension and the direct adverse effects of insulin-resistance, hyperinsulinemia and hyperglycemia on the myocardium. Diabetes mellitus occurs in 12-47% of patients with CHF and can develop within several years after a diagnosis of HF in 22% of patients due to insulin-resistance of failure tissues. The presence of diabetes mellitus leads to a greater severity of clinical symptoms and hospitalization rate, worsening of quality of life and prognosis in CHF. A decreased left ventricular ejection fraction is an independent predictor of the poor prognosis in the patients with diabetes mellitus. The algorithm of the treatment of CHF in the patients with and without diabetes mellitus is not fundamentally different, but it requires taking into account the metabolic effects of the prescribed drugs. Angiotensin receptor-neprilysin inhibitor are increasingly used in clinical practice and are gradually replacing angiotensin-converting enzyme inhibitors and sartans in CHF both without diabetes mellitus and in its presence. Recently, the effectiveness of type 2 sodium glucose cotransporter inhibitors has been proven in patients with CHF with and without diabetes mellitus. This review is devoted to the relationship of diabetes mellitus and CHF, as well as the approaches to the management of such comorbid patients.